It Shouldn't be this Hard

Geometry Level 4

In A B C , C A B = 6 0 , A = ( 0 , 0 ) \triangle{ABC}, \angle{CAB} = 60^\circ, A = (0,0) . Side B C BC passes through point P = ( 3 , 3 ) P = (3,3) . Given these constraints, what is the shortest length of B C BC ? Submit 1 0 5 B C \lfloor{10^5\cdot{\overline{BC}}\rfloor}


The answer is 462585.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Pi Han Goh
Oct 29, 2020

Let the x x -coordinate of B B be n > 0 n>0 , and since the ratio of the y y -coordinate and the x x -coordinate of the coordinate C C is tan ( 6 0 ) = 3 \tan(60^\circ) = \sqrt3 , we can denote the coordinate of C C to be ( m , m 3 ) \left(m, m\sqrt3\right) , where 0 < m 3 0<m\leqslant 3 .

Define D D as the square of the distance B C BC , then using the distance formula , D = ( m 3 ) 2 + ( m n ) 2 = 3 m 2 + ( m n ) 2 . D = (m\sqrt3)^2 + (m-n)^2 = 3m^2 + (m-n)^2.

Since P ( 3 , 3 ) P(3,3) passes through the straight line B C BC , the gradients of the straight line C P , P B , B C CP, PB, BC are all identical: m 3 3 m 3 = 3 3 n = m 3 m n . \dfrac{m\sqrt3 - 3}{m-3} = \dfrac3{3-n} = \dfrac{m\sqrt3}{m-n}.

Setting n n as the subject gives n = 3 m m 3 3 ( m 3 1 ) . n = \dfrac{3m}{m\sqrt3 - 3} \left(m \sqrt3 - 1\right) .

Thus, upon substitution, we can express D D as a single variable function, D = 6 m 2 ( 2 m 2 3 ( 1 + 3 ) m + 9 ) ( m 3 3 ) 2 . D= \dfrac{6m^2 (2m^2 - 3(1 + \sqrt3) m + 9)}{(m \sqrt3 - 3)^2} .

At the critical point, d d m D = 0 m ( 24 3 ) m 3 + m 2 ( 198 18 3 ) + m ( 162 + 162 3 ) 324 3 3 m 3 27 m 2 + 27 3 m 27 = 0 \dfrac {d}{dm} D = 0 \quad \implies \quad m \cdot \dfrac{(24 \sqrt3) m^3 + m^2 (-198 - 18\sqrt3) + m(162 + 162\sqrt3) - 324}{3 \sqrt3 m^3 - 27 m^2 + 27 \sqrt3 m - 27} = 0

Simplifying this gives m 3 ( 4 3 ) + m 2 ( 33 3 3 ) + m ( 27 + 27 3 ) 54 = 0 m^3 (4\sqrt3) + m^2 (-33 - 3\sqrt3) + m(27 + 27\sqrt3) - 54 = 0 . Using Cardano's method , we get m = 11 + 3 4 3 + q 27648 6 7 3 8 6912 6 q 2.504653757 , m = \dfrac{11 + \sqrt3}{4\sqrt3} + \dfrac q{\sqrt[6]{27648}} - \dfrac{7\sqrt3 - 8}{\sqrt[6]{6912} \cdot q} \approx 2.504653757, where q = 391 195 3 + 258876 147744 3 3 q = \sqrt[3]{391 - 195 \sqrt3 + \sqrt{258876 - 147744 \sqrt3}} .

Checking the endpoints of the domain 0 < m 3 0 < m \leqslant 3 , the critical point of D ( 2.504653757 ) D(2.504653757) is smaller than D ( 0 ) D(0) and D ( 3 ) D(3) . Hence, this critical point must be a minimum value.

We have min ( D ) 21.39856894117064819658652 \min(D) \approx 21.39856894117064819658652 with coordinates B ( 4.1104861276 , 0 ) , C ( 2.504653757949 , 4.338187564 ) . B \approx (4.1104861276 , 0), \quad \quad C \approx (2.504653757949, 4.338187564).

The answer is 1 0 5 21.398568941170648196586523 = 462585 . \left \lfloor 10^5 \cdot \sqrt{21.398568941170648196586523\ldots} \right \rfloor = \boxed{462585}.


Addendum:

  1. Even if we allow n < 0 n< 0 , that is, the x x -coordinate of B B is negative, then the straight line B C BC can never pass through ( 3 , 3 ) (3,3) . A simple graphing shows that the straight A C AC and B C BC does not intersect at the coordinate C C .

  2. The maximum value of the length B C BC is 3 3 3\sqrt3 , and it occurs when A B C ABC is a right triangle at B \angle B , with m = n = 3 m=n = 3 .

Holy smokes, you are fast! It took me several days. Nice work, Pi Han.

Fletcher Mattox - 7 months, 2 weeks ago
Chew-Seong Cheong
Oct 30, 2020

Let B = θ \angle B = \theta . By sine rule, C P A P = sin C A P sin A C P = sin 1 5 sin ( 12 0 θ ) = sin 1 5 sin ( 6 0 + θ ) \dfrac {CP}{AP} = \dfrac {\sin \angle CAP}{\sin \angle ACP} = \dfrac {\sin 15^\circ}{\sin (120^\circ - \theta)} = \dfrac {\sin 15^\circ}{\sin (60^\circ + \theta)} . And B P A D = sin P A B sin P B A = sin 4 5 sin θ \dfrac {BP}{AD} = \dfrac {\sin \angle PAB}{\sin \angle PBA} = \dfrac {\sin 45^\circ}{\sin \theta} . C P B P = sin 1 5 sin θ sin 4 5 sin ( 6 0 + θ ) \implies \dfrac {CP}{BP} = \dfrac {\sin 15^\circ \sin \theta}{\sin 45^\circ \sin (60^\circ + \theta)} .

Let B C = a BC=a . Then C P B P = a sin θ 3 3 = sin 1 5 sin θ sin 4 5 sin ( 6 0 + θ ) \dfrac {CP}{BP} = \dfrac {a\sin \theta - 3}3 = \dfrac {\sin 15^\circ \sin \theta}{\sin 45^\circ \sin (60^\circ + \theta)} and:

a = 3 sin 1 5 sin θ + 3 sin 4 5 sin ( 6 0 + θ ) sin 4 5 sin θ sin ( 6 0 + θ ) = 3 ( cos ( θ 1 5 ) cos ( θ + 10 5 ) ) sin 4 5 ( cos 6 0 cos ( 2 θ + 6 0 ) ) = 3 sin 6 0 sin ( θ + 4 5 ) sin 4 5 ( cos 6 0 cos ( 2 θ + 6 0 ) ) = 6 6 sin ( θ + 4 5 ) 1 2 cos ( 2 θ + 6 0 ) d a d θ = 6 6 ( cos ( θ + 4 5 ) ( 1 2 cos ( 2 θ + 6 0 ) ) 4 sin ( θ + 4 5 ) sin ( 2 θ + 6 0 ) ) ( 1 2 cos ( 2 θ + 6 0 ) ) 2 \begin{aligned} a & = \frac {3 \sin 15^\circ \sin \theta+ 3 \sin 45^\circ \sin (60^\circ + \theta)}{\sin 45^\circ \sin \theta \sin (60^\circ + \theta)} \\ & = \frac {3(\cos (\theta - 15^\circ)-\cos(\theta + 105^\circ))}{\sin 45^\circ (\cos 60^\circ - \cos (2\theta + 60^\circ))} \\ & = \frac {3\sin 60^\circ \sin (\theta + 45^\circ)}{\sin 45^\circ(\cos 60^\circ - \cos (2\theta + 60^\circ))} \\ & = \frac {6\sqrt 6 \sin (\theta + 45^\circ)}{1 - 2\cos (2\theta + 60^\circ)} \\ \frac {da}{d\theta} & = \frac {6\sqrt 6 (\cos (\theta + 45^\circ)(1 - 2\cos (2\theta + 60^\circ)) - 4 \sin (\theta + 45^\circ)\sin (2\theta + 60^\circ))}{(1 - 2\cos (2\theta + 60^\circ))^2} \end{aligned}

As there is no maximum value of a a , to find min ( a ) \min (a) , we find the θ \theta such that d a d θ = 0 \dfrac {da}{d\theta} = 0 .

cos ( θ + 4 5 ) ( 1 2 cos ( 2 θ + 6 0 ) ) = 4 sin ( θ + 4 5 ) sin ( 2 θ + 6 0 ) 1 2 cos ( 2 θ + 6 0 ) 4 sin ( 2 θ + 6 0 ) = tan ( θ + 4 5 ) 1 cos 2 θ + 3 sin 2 θ 2 3 cos 2 θ + 2 sin 2 θ = 1 + tan θ 1 tan θ Let t = tan θ 1 + t 2 1 + t 2 + 2 3 t 2 3 2 3 t 2 + 4 t = 1 + t 1 t 3 t + t 2 3 + 2 t 3 t 2 = 1 + t 1 t ( 3 1 ) t 3 t 2 2 t 3 = 0 \begin{aligned} \cos (\theta + 45^\circ)(1 - 2\cos (2\theta + 60^\circ)) & = 4 \sin (\theta + 45^\circ)\sin (2\theta + 60^\circ) \\ \frac {1 - 2\cos (2\theta + 60^\circ)}{4\sin (2\theta + 60^\circ)} & = \tan (\theta + 45^\circ) \\ \frac {1-\cos 2\theta + \sqrt 3\sin 2\theta}{2\sqrt 3\cos 2\theta + 2\sin 2\theta} & = \frac {1+\tan \theta}{1-\tan \theta} & \small \blue{\text{Let }t = \tan \theta} \\ \frac {1+t^2 - 1 + t^2 + 2\sqrt 3t}{2\sqrt 3 - 2\sqrt 3 t^2 + 4t} & = \frac {1+t}{1-t} \\ \frac {\sqrt 3t + t^2}{\sqrt 3 + 2t - \sqrt 3 t^2 } & = \frac {1+t}{1-t} \\ (\sqrt 3-1)t^3 - t^2 - 2t - \sqrt 3 & = 0 \end{aligned}

Solving the cubic equation, we have t 2.701519565 t \approx 2.701519565 and min ( a ) = 3 2 ( 1 + t ) 1 + t 2 3 t + t 2 4.625858725 \min (a) = \dfrac {3\sqrt 2(1+t)\sqrt{1+t^2}}{\sqrt 3t +t^2} \approx 4.625858725 . Therefore 1 0 5 min ( a ) = 462585 \lfloor 10^5 \min(a)\rfloor = \boxed{462585} .

David Vreken
Oct 30, 2020

Draw A P AP , which by the distance formula a length of A P = ( 3 0 ) 2 + ( 3 0 ) 2 = 3 2 AP = \sqrt{(3 - 0)^2 + (3 - 0)^2} = 3\sqrt{2} .

Since by the slopes formula tan P A B = 3 0 3 0 \tan \angle PAB = \frac{3 - 0}{3 - 0} , A P B = 45 ° \angle APB = 45° , this makes P A C = C A B P A B = 60 ° 45 ° = 15 ° \angle PAC = \angle CAB - \angle PAB = 60° - 45° = 15° .

Let θ = A P B \theta = \angle APB . Then from the straight line A P C = 180 ° θ \angle APC = 180° - \theta and by the angle sums of A P C \triangle APC and A P B \triangle APB , P B A = 135 ° θ \angle PBA = 135° - \theta and P C A = θ 15 ° \angle PCA = \theta - 15° .

By the law of sines on A P C \triangle APC , C P = 3 2 sin 15 ° sin ( θ 15 ° ) CP = \cfrac{3\sqrt{2} \sin 15°}{\sin (\theta - 15°)} , and by the law of sines on A P B \triangle APB , P B = 3 2 sin 45 ° sin ( 135 ° θ ) PB = \cfrac{3\sqrt{2} \sin 45°}{\sin (135° - \theta)} , so B C = 3 2 sin 15 ° sin ( θ 15 ° ) + 3 2 sin 45 ° sin ( 135 ° θ ) BC = \cfrac{3\sqrt{2} \sin 15°}{\sin (\theta - 15°)} + \cfrac{3\sqrt{2} \sin 45°}{\sin (135° - \theta)} .

The minimum will occur when d B C d θ = 3 2 sin 15 ° cos ( θ 15 ° ) sin 2 ( θ 15 ° ) + 3 2 sin 45 ° cos ( 135 ° θ ) sin 2 ( 135 ° θ ) = 0 \cfrac{dBC}{d\theta} = \cfrac{3\sqrt{2} \sin 15° \cos (\theta - 15°)}{- \sin^2 (\theta - 15°)} + \cfrac{3\sqrt{2} \sin 45° \cos (135° - \theta)}{\sin^2 (135° - \theta)} = 0 , which solves numerically to θ 65.3126396562 ° \theta \approx 65.3126396562° .

Substituting θ \theta value into the equation for B C BC gives B C 4.625858725 BC \approx 4.625858725 , so 1 0 5 B C = 462585 \lfloor 10^5 \cdot BC \rfloor = \boxed{462585} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...